Ameloblastoma and keratocyst : Statistical analysis of cases (Mustansiria Dental Journal, 2018)
Seventy four cases of odontogenic ameloblastoma (OA) and forty three cases of odontogenic keratocyst (OKC) were obtained from the files of the Department of Oral Pathology, College of Dentistry, Baghdad University covering the period from 1980 to 1990.The cases were analyzed according to sex, age and location. Results showed that males were affected by OA 45(60.8%) and OKC 24(55.8%) more than females 29(39.2%),19(44.2%), respectively. In this study OA occurred more frequently in 21-30 years age group 25(33.8%).Regarding OKC the most affected age group were 21-30 years and 11-20 years 12(27.9%) and 8(18.6%), respectively .The mandible was the most frequent site of involvement for both OA 65(87.8%) and OKC 27(62.8%).Most of the findings in the present study agreed with previous available data from the literatures.